Clinical appearance of acute pseudomembranous candidiasis in children and the importance of good communication, information and education to patients: A case report - Afryla Femilian; Winda Dwi Malinda Masuku; Nurina Febriyanti Ayuningtyas; Diah Savitri Ernawati; Fatma Yasmin Mahdani; Meircurius Dwi Condro Surboyo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Oral candidiasis is a common opportunistic infection of the oral cavity caused by an overgrowth of the Candida species, in particular, Candida albicans. The incidence varies depending on age and certain predisposing factors. In the practice of dentistry, doctor-patient communication is an important component. Effective communication between doctor and patient is needed to convey information and educate patients so that treatment can be administered appropriately. Purpose: This case aimed to discuss the clinical appearance of acute pseudomembranous candidiasis (APC) in children and the importance of good communication, information and education of patients. Case: A five-year-old male patient came with his mother on November 6, 2020 complaining of white deposits on the mucosa of the upper and lower lips that had been present for a week. Case management: The diagnosis was defined as a typical APC lesion although the potassium hydroxide (KOH) test showed negative results. Characteristic lesions found in APC are often seen clearly in some cases and treatment can begin immediately. Patients receive the empirical therapy, Nystatin oral suspension 100.000 i.u, and the patient is instructed to maintain optimal oral hygiene care, maintain nutrient intake and book a follow-up consultation. Conclusion: Mistakes in patient preparation procedures in taking supporting examinations will result in false negative/positive results, so communication and education information regarding the preparation of supporting examinations for patients is important to note.